Re-Running the Rising: Centenary Stagings - Grene, Nicholas (Hungarian Journal of English and American Studies, 2020)
Drawing on his experience as an Irish Times Theatre Awards judge through 2016, the author analyzes a range of shows relating to the Easter Rising produced in Irish theatre in that centenary year. The aim is to show their variety of styles, realistic and experimental, but also the political viewpoints, whether belonging to a traditional nationalist historiography or its revisionist alternative. Some of the plays maintained the conservative representational dramaturgy so characteristic of much Irish drama, but more worked with dance, song, and video in theatrical mixed modes, including a radically innovative production of Sean O’Casey’s The Plough and the Stars at the Abbey Theatre. Site-specific shows sought to immerse audiences in the original experiences of the Rising, while the most formally experimental plays avoided direct representation altogether. The political positions were as varied as the theatrical styles from conventional nationalist hagiography to those which questioned the value and meaning of the Rising.